THE COLORFUL TREND OF COLORS IN PANIKKAR’S WORKS: पणिक्कर की कृतियों में रंगों का रसात्मक रूझान - Gupta, Garima (International Journal of Research -GRANTHAALAYAH, 2014)
We all are widely affected by colors in our lives. The effect of colors can be seen in the stimulation of our emotions like our happiness, sorrow, excitement, relaxation, joy. In painter language, colors are short forms of emotion and thought. Each painter’s method of using color is influenced by personal experience and interest, the painter uses the power of color to convey the meaning of the picture with his or her sensible technique. In this world, that Param Shakti has created many things. Probably even their number could not be counted throughout life. Different types of stones are known for their color and form and touch. In the same way, the string-flow of wood, the color and the surface, the softness of the flowers and the taste of the color provide a pleasant feeling to the viewer. हम सभी अपने जीवन में रंग¨ंे से व्यापक रूप में प्रभावित ह¨ते हैं हमारे सुख-दुख, उत्त्¨जना, विश्राम, उल्लास आदि सभी भावनाअ¨ं के उद्दीपन में रंग¨ं का प्रभाव देखा जा सकता है। चित्र्ाकार की भाषा में रंग भावना एवं विचार के संक्षिप्त रूप ह¨ते हैं। प्रत्येक चित्र्ाकार द्वारा रंग¨ंे क¨ प्रय¨ग करने की विधि व्यक्तिगत अनुभव अ©र रुचि से प्रभावित ह¨ती हैं, चित्र्ा के अर्थसार क¨ व्यक्त करने मंे चित्र्ाकार रंग की सामथ्र्य का उपय¨ग अपनी अनुभूत तकनीक से करता है। इस भ©तिक जगत में उस परम् शक्ति ने अनेक वस्तुअ¨ं का निर्माण किया है। सम्भवतया जीवन भर उनकी संख्या भी न गिनाई जा सके। विभिन्न प्रकार के पत्थर उनके वर्ण तथा रूप एवं स्पर्श ज्ञान ह¨ते हैं। इसी प्रकार लकड़िय¨ं के रेश्¨-प्रवाह, वर्ण तथा धरातल, फूल-पत्तिय¨ं की मृदुता तथा वर्ण का आस्वादन दर्शक क¨ सुखद अनुभूतियाँ प्रदान करता हैं।